1997
DOI: 10.1016/s0194-5998(97)70038-x
|View full text |Cite
|
Sign up to set email alerts
|

Mastoidectomy in noncholesteatomatous chronic suppurative otitis media: Is it necessary?

Abstract: Chronic suppurative otitis media (CSOM) without cholesteatoma, the surgical treatment of which is still controversial, is a common diagnosis in otologic practice. A retrospective analysis of 323 patients who underwent surgery for noncholesteatomatous chronic otitis media in the Gruppo Otologica, Piacenza, Italy, between April 1983 and December 1993 is presented. Cases were separated into three groups according to different surgical treatment modalities and conditions of the ears at the time of operation. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 5 publications
4
91
1
2
Order By: Relevance
“…Balyan et al [25] operated discharging ear with sclerotic mastoid and showed that there was no statistically significant differences between the outcome of myringoplasty in patients who had undergone simple mastiodectomy plus myringoplasty and those without mastoidectomy. But in the study of Puhakka et al [8] the results were significantly poor if preoperative X-Ray mastoid was sclerotic.…”
Section: Graft Successmentioning
confidence: 99%
“…Balyan et al [25] operated discharging ear with sclerotic mastoid and showed that there was no statistically significant differences between the outcome of myringoplasty in patients who had undergone simple mastiodectomy plus myringoplasty and those without mastoidectomy. But in the study of Puhakka et al [8] the results were significantly poor if preoperative X-Ray mastoid was sclerotic.…”
Section: Graft Successmentioning
confidence: 99%
“…10 In a study done by Toros et al tympanic membrane perforation closure was successful in 76.1% of the 46 patients undergoing myringoplasty and in 78.3% (n=36) of the 46 patients undergoing Myringoplasty with mastoidectomy. The difference between the closure rates of the two groups was not statistically significant (p>0.05).…”
Section: Discussionmentioning
confidence: 94%
“…Some authors believe that mastoidectomy is not necessary for treatment of all non cholesteatomatous ears 7 . However, some believe that addition of mastoidectomy greatly increases the success of tympanoplasty 8 .…”
Section: Discussionmentioning
confidence: 99%